1993
DOI: 10.1111/j.1532-950x.1993.tb00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Closed‐Circuit Liquid Injection Isoflurane Anesthesia in the Horse

Abstract: Six horses were administered isoflurane anesthesia by liquid injection into a closed breathing circuit according to the square root of time model. The unit dose (UD) was calculated using Lowe's formula to provide an end-tidal concentration of 1.3%, or the minimum alveolar concentration of isoflurane. The mean UD was 4.2 +/- 0.2 mL. The mean end-tidal isoflurane concentration (ETiso) for each interval after injection, and the peak and minimum concentrations for each injection interval, did not change beginning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…This suggests that the intervals between injections proposed by Lowe were over‐long. The results contrast with the situation in horses in which the square‐root‐of‐time model evaluated by liquid injection of isoflurane produced constant end‐tidal concentrations for 100 minutes (Olson et al. 1993).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…This suggests that the intervals between injections proposed by Lowe were over‐long. The results contrast with the situation in horses in which the square‐root‐of‐time model evaluated by liquid injection of isoflurane produced constant end‐tidal concentrations for 100 minutes (Olson et al. 1993).…”
Section: Discussioncontrasting
confidence: 67%
“…Some of these authors found the square‐root‐of‐time model accurately predicted anaesthetic uptake while others judged it to be an inadequate or potentially harmful means of achieving closed system anaesthesia, finding alveolar anaesthetic concentrations to differ markedly from predicted values. The square‐root‐of‐time model has been evaluated in dogs with halothane and isoflurane (Moens 1988) and in horses with isoflurane (Olson et al. 1993) and is considered useful for performing closed circuit anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…As is shown by the high correlation coefficient between the amount of Iso used to produce 1 hour of anaesthesia and horse weight, the ETCLo-TCI system produces quantitative volatile agent anaesthesia. Although quantitative anaesthesia is often associated, as shown in the literature, with the use of a closed-circuit breathing system [6], it has not previously been demonstrated for an ETCLo-TCI system. One advantage of the tested delivery system is that it is able to adapt the anaesthetic administered to the FGF set by the anaesthetist, because the FGF is used in Equation (2) to calculate the amount of Iso that has to be delivered One advantage of the tested delivery system is that it is able to adapt the anaesthetic administered to the FGF set by the anaesthetist as per Equation (2).…”
Section: Discussionmentioning
confidence: 98%
“…In order to avoid a potentially serious cardiovascular consequence, as previously reported [6], the loading dose was administered over 2 minutes. This can explain why there was no significant difference in the time taken by both systems to reach the FE'Iso target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation